Thermodynamic and economic analysis of hydrogen production integration in the Brazilian sugar and alcohol industry - Silveira, Jose Luz [UNESP]; Tuna, Celso Eduardo [UNESP]; Lamas, Wendell de Queiroz [UNESP]; Silva, Marcio Evaristo da [UNESP]; Martinelli, Valdisley Jose [UNESP] (Elsevier B.V., 2014)
One of the biggest challenges today is to develop clean fuels, which do not emit pollutant and with viable implementation. One of the options currently under study is the hydrogen production process. In this context, this work aims to study the technical and economical aspects of the incorporation process of hydrogen producing by ethanol steam reforming in the sugar cane industry and MCFC (molten carbonate fuel cell) application on it to generate electric power. Therefore, it has been proposed a modification in the traditional process of sugar cane industry, in order to incorporate hydrogen production, besides the traditional products (sugar, ethylic, hydrated and anhydric alcohol). For this purpose, a detailed theoretical study of the ethanol production process, describing the considerations to incorporate the hydrogen production will be performed. After that, there will be a thermodynamic study for analysing the innovation of this production chain, as well as a study of economic engineering to allocate the costs of products of the new process, optimising it and considering the thermoeconomics as being as an analysis tool. This proposal aims to improve Brazil's position in the ranking of international biofuels, corroborating the nation to be a power in the hydrogen era. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: DIR-MCFC; Electrical power generation; Ethanol steam reforming; Renewable energy; Technical analysis